Intercultural Based Global Curriculum Development to Enhance Multilingual Students’ Competencies in the Era of Digitalization and International Mobility - Martina Rosmaulina Marbun; Ainur Rofiq Sofa; Welsi Damayanti (International Forum of Researchers and Lecturers, 2024)
This study focuses on developing a global curriculum model that integrates intercultural and multilingual competencies to enhance students’ academic and communicative skills. The proposed framework emphasizes flexibility, inclusivity, and adaptability, combining theoretical knowledge with practical applications to help students thrive in multicultural, multilingual, and digitally mediated global contexts. Using a qualitative curriculum design approach, the study examines the integration of intercultural competence and multilingual education into existing curricula, offering a model adaptable to diverse educational settings. It further explores the impact of this curriculum on students' ability to communicate across cultural and linguistic boundaries, highlighting the importance of digital literacy and global communication skills. The findings indicate that the intercultural model enhances students' academic performance and global citizenship, preparing them for international collaborations and addressing global challenges. Additionally, the curriculum's adaptability ensures its alignment with digital education demands, making it relevant in today’s evolving educational landscape. The research underscores the importance of curricula that embrace cultural diversity and linguistic multiplicity, promoting inclusivity and preparing students for the complexities of an interconnected world. The study concludes with practical recommendations for educators, policymakers, and curriculum developers to implement intercultural and multilingual frameworks globally, ensuring students are equipped with the necessary skills for success in the digital and globalized world.